2013
DOI: 10.3109/00365513.2012.762114
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-induced coagulopathy is less severe and more effectively reversed with fibrinogen concentrate than is synthetic colloid-induced coagulopathy

Abstract: Introduction Autophagy is well known as one of the biogenic responses against various stresses, which possesses the benefi cial roles for survival, but little is known about the dynamics and its signifi cance during the septic condition. We hypothesized that autophagy is induced during the septic condition, and contributes to protect from tissue damage which subsequently leads to organ dysfunction. We confi rm whether the autophagic process is accelerated or sustained in an acute phase of sepsis and we also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
4
21
0
2
Order By: Relevance
“…The degree of impairment of ROTEM parameters induced by haemodilution with albumin is in agreement with an earlier study from our group [9]. It has previously been shown that addition of FXIII alone has no or little effect on ROTEM parameters following haemodilution with either Ringer's solution [17,18] or gelatin [21], and our results suggest that this is also the case for the natural colloid albumin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The degree of impairment of ROTEM parameters induced by haemodilution with albumin is in agreement with an earlier study from our group [9]. It has previously been shown that addition of FXIII alone has no or little effect on ROTEM parameters following haemodilution with either Ringer's solution [17,18] or gelatin [21], and our results suggest that this is also the case for the natural colloid albumin.…”
Section: Discussionsupporting
confidence: 92%
“…However, colloids such as albumin, gelatin, hydroxyethyl starch (HES) and dextran confer advantages over crystalloids, including enhanced duration of haemodynamic effects and less capillary leakage [7,8]. A number of studies have shown that synthetic colloids including gelatin, hydroxyethyl starches and dextran, affect haemostatic parameters in whole blood viscoelastic tests (thromboelastography [ ]), to a greater extent than albumin [9][10][11][12][13][14]. Therefore, an initial volume substitution regime with 4-5% albumin, together with a restricted crystalloid regime, may be favourable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a somewhat controversial result considering it has been suggested that albumin is no worse than saline, having less effect on hemostasis than other synthetic colloids. 35 However, a previous in vitro study which investigated the effect of dilution with albumin compared to starch in whole blood, similar to the present study, has also shown that albumin caused the greatest derangement in clotting. 7 Another study has also reported that albumin has a heparin-like effect on coagulation.…”
Section: -27mentioning
confidence: 43%
“…cardiac surgery patients with extracorporeal circulation) the application of albumin is possible since no substance-specific alterations regarding coagulation have been reported for human albumin use. However, the administration of large amounts of albumin can also cause a dilutional coagulopathy [116]. …”
Section: Human Albuminmentioning
confidence: 99%